PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, DAN OPINI AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAN SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017–2019 - Siagian, Putri Aningsih; Simorangkir, Enda Noviyanti; Mazruk, Nura Achmad (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2021)
The purpose of this study is to determine and analyze whether firm size, profitability, solvency, and audit opinion affect or not on audit delay. Audit delay occurs because of a negative impact on timeliness, affecting the relevance of information obtained from accounting. The sample determination was carried out using a purposive sampling method so that a total of 48 samples of companies listed on the Indonesia Stock Exchange were obtained in the various industrial sectors with the 2017-2019 research period. This research uses the multiple linear regression analysis method. This study indicates that firm size and audit opinion negatively and significantly affect audit delay, profitability does not significantly affect audit delay, and solvency has a positive and significant impact on audit delay.